The genus Guernea Chevreux, 1887 from Korean waters (Crustacea: Amphipoda: Dexaminidae) - Kim, Young-Hyo; Hendrycks, Ed A.; Lee, Kyung-Sook (Zootaxa, 2011)
Four species of the dexaminid genus Guernea are reported from Korean coastal waters. This is the first record of the genus Guernea from Korea. Two of the species are identified as new species; Guernea jejuensis and Guernea namhaensis. The remaining two Japanese species Guernea ezoensis Ishimaru, 1987 and Guernea nullispina Hirayama, 1985 are new records for Korean waters. The species are fully illustrated and detailed comparisons are made with related species. A key to north Pacific Guernea species is also provided.